Bio-Inspired Technology - Srivastava, Ruby (IntechOpen, 2019)
Biomimetic devices are designed and produced by materials, structures, and systems that are modelled on biological entities and processes. These devices are used to synthesize novel materials and their functions at the multiscale level for various applications. Molecular computing biological devices play a key role in the logical processing of the cellular machinery of all living organisms. This book includes information on both biomedical and technological applications of bioactive devices for hard tissue regeneration; design of chip-based disease diagnostic platforms; neuromorphic computing biomaterials that transfer techniques of neuroscience to a silicon chip; various top-down and bottom-up designs; and electrical characterization and transport mechanisms of DNA as nanowires.